Bifurcated homeland and diaspora politics in China and Taiwan towards the Overseas Chinese in Southeast Asia. Issue 4 (12th March 2019) - Han, Enze
ABSTRACT: The conventional literature on diaspora politics tends to focus on one 'homeland' state and its relations with 'sojourning' diaspora around the world. This paper examines an instance of 'bifurcated homeland:' the People's Republic of China and the Republic of China (Taiwan) since 1949. The paper investigates the changing dynamics of China's and Taiwan's diaspora policies towards Overseas Chinese communities in Southeast Asia throughout the Cold War and post-Cold War periods. They were affected by their ideological competition, the rise of Chinese nationalism, and the 'indigenisation' of Taiwanese identity. Illustrating such changes through the case of the KMT Yunnanese communities in Northern Thailand, this paper makes two interrelated arguments. First, we should understand relations through the lens of interactive dynamics between international system-level changes and domestic political transformations. Depending on different normative underpinnings of the international system, the foundations of regime legitimacy have changed. Subsequently, the nature of relations between the diaspora and the homeland(s) transformed from one that emphasises ideological differences during the Cold War, to one infused with nationalist authenticity in the post-Cold War period. Second, the bifurcated nature of the two homelands also created mutual influences on their diaspora policies during periods of intense competition.